Design Battery Charger With CC-CV Method for Series Connected Lithium-Ion Batteries Using Fuzzy Logic Controller - Sutedjo, Sutedjo; Rakhmawati, Renny; Putih, Bening Putri Permata; Adila, Ahmad Firyal; Irianto, Irianto; Yanaratri, Diah Septi (Department of Electrical Engineering ITS and FORTEI, 2025)
Considering the many human needs, the existence of solar energy is considered very appropriate to help meet the energy needs consumed by humans. All the energy produced by solar panels can be stored using batteries which can then be converted into electrical energy. The battery will work when the energy stored in the battery is fulfilled, but if the use of the battery is carried out continuously it causes the energy in the battery to run out, so that the battery energy must be recharged immediately so that it can still be used again. charging which is used to recharge battery energy at this time unfortunately it still takes quite a long time to be recharged. Through the description of the problem, so that in study this is a tool fast charging use buck converter by using the method (Constant Current) CC-CV (Constant Voltage) on a Lithium-Ion battery. Buck converter This is necessary because the source used in this study is a solar panel which produces a very high voltage, so the voltage needs to be lowered by using buck converter. Using a 11.1V / 2.2 Ah LithiumIon battery. To keep the current and voltage constant, the charging process is carried out charging this current and voltage the output will be stabilized by Fuzzy Logic Controller (FLC). From the simulation results that have been carried out, it appears that the FLC has been able to stabilize the charging current of 2.2Ah and 11.1V.